Stability and Bifurcation Analysis of Time Delayed Prey-Predator System with Holling Type-III Response Function - Nur Aina Maziun; Subchan Subchan (LPPM Institut Teknologi Sepuluh Nopember, 2020)
Interaction between prey and predator is a recurring event that occurs continuously and the presence of both can mutually affect each other’s population. This paper discusses the stability and bifurcation analysis of time delayed prey-predator system with Holling type-III response function incorporating a prey refuge. Holling type-III response function is used because the availability of the prey in nature is decreasing. Time delay represents the time for predators to find another prey population when the available population is decreasing. Dynamic analysis is used to study the influence of a given response function. The equilibrium point and stability analysis of the model with and without time delay has been calculated and analyzed. Model analysis under the influence of time delay and coefficient of competition among predators shows an indication of Hopf bifurcation in the neighborhood of the co-existing equilibrium point.